2021
DOI: 10.1159/000521167
|View full text |Cite
|
Sign up to set email alerts
|

Exosome miR-23a-3p from Osteoblast Alleviates Spinal Cord Ischemia/Reperfusion Injury by Down-Regulating KLF3-Activated CCNL2 Transcription

Abstract: Background: Spinal cord ischemia/reperfusion injury (SCIRI) is usually caused by spinal surgery or aortic aneurysm surgery and can eventually lead to paralysis or paraplegia and neurological dysfunction. Exosomes are considered as one of the most promising therapeutic strategies for SCIRI as they can pass the blood-spinal barrier. Previous studies have proved that exosomes secreted by osteocytes have a certain slowing effect on SCIRI. Aim: We aimed to explore the effect of osteoblast secreted exosomes on SCIRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…EVs could be used to treat spinal cord contusion, compression, and transection (Mu et al, 2021 ). Furthermore, they could treat spinal cord ischemia/reperfusion injury because of their ability to pass the blood-spinal barrier (Wu et al, 2022 ). A meta-analysis showed that EVs were more effective in treating contusion models as compared with compression models (Yi and Wang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…EVs could be used to treat spinal cord contusion, compression, and transection (Mu et al, 2021 ). Furthermore, they could treat spinal cord ischemia/reperfusion injury because of their ability to pass the blood-spinal barrier (Wu et al, 2022 ). A meta-analysis showed that EVs were more effective in treating contusion models as compared with compression models (Yi and Wang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%